Engineering and management approach in the sphere of transport and logistics - A. A. Stepanov; Ya. S. Ignatova; A. O. Merenkov; G. A. Lastochkina; A. V. Malkova (Вестник университета)
The article is devoted to the analysis (consideration) of peculiarities of management in the sphere of transport at the present stage of social and technological development. The role of transport and infrastructure projects as a key element of the country’s economic development is described. Being linked into a single comprehensive plan, infrastructure solutions become the basis for the development of a country or territory. It was concluded that with the current form of organisation of transport activities, a two-circuit management system is believed to be optimal, when the role of the state is reduced to planning of long cycles and to the role of economic administrator. The private sector, individual carriers, small companies regulate the quality of service by individualising the supply. One of the most important points of contact between these systems is the sphere of education. The authors describe the concept of engineering and management approach to education. This approach will make it possible to systematically train specialists with both technological and managerial competencies which will become an impetus for the development of economic sectors and strengthening the technological sovereignty of the state. The purpose of the article is to determine the patterns of functioning of the transport and logistics sphere in the framework of supply-side economics, and to consider the engineering and management approach to the training of specialists (for the industry).